Safety Evaluation of Insufficient Lining Thickness Based on Fuzzy Comprehensive Evaluation in Tunnel - Wang, Yiming; Mansor, Hazrina; Krishta David, Thevaneyan (International Journal of Sustainable Construction Engineering and Technology, 2024)
This paper presents a study on the safety evaluation of the lining structure with insufficient thickness based on a fuzzy comprehensive evaluation model in railway tunnels. Determining weight and membership degree are two critical points of this evaluation method. These two points are determined using an improved method: field data analysis and numerical simulation. Most conventional determination methods are based on subjective judgment, while the method in this paper is based on engineering practice. Field data analysis revealed that the proportion of defects in the surrounding rocks of class ? and at the vault was the largest. Defect length between 3m and 4.5m and thickness ratio between 0.55 and 0.7 occupied the most significant proportion. Numerical simulation was also used to study the effect of the parameter changes on structural safety. It is known that the change of defect lengths has a not very obvious effect on the safety factor of the lining. In contrast, the changes in the other three parameters can significantly impact the lining. The factor set and comment set are determined according to the characteristic indicators from the collected field data. The membership degree and weight set are determined according to the previous statistical analysis and numerical analysis results. The fuzzy comprehensive evaluation model is established, and the structural safety evaluation work can be conducted. Then this model is validated by means of the numerical simulation based on the evaluation work of the specific engineering case.